Production of nanopowders of oxides by means of fiber and pulse‐periodical CO2 lasers. Issue 6 (2nd May 2013) - Osipov, V. V.; Platonov, V. V.; Lisenkov, V. V.; Podkin, A. V.; Zakharova, E. E.; Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
Abstract The results of investigation of YSZ, Nd:Y2O3, Al2O3 nanopowder production by laser evaporation of oxide targets in a gas current are reported in present paper. For this purpose we used the pulse‐periodical CO2 laser and the continuous fiber ytterbium laser with 550 W and 600 W radiation mean power accordingly. The powders obtained by these lasers, consisted of weakly agglomerated spherical nanopartices (≥ 99 wt%), and ≤ 1 wt% of micron sized particles (drops and target fragments). Nanoparticles from various oxides produced by CO2 laser in atmospheric pressure air had close average sizes (10÷16 nm). The productivity of nanopowder synthesis by CO2 laser from YSZ 1%Nd:Y2O3, 1%Nd:Y2O3, Al2O3, and CeGdO was 23 g/hour, 29 g/hour, 24 g/hour and 80 g/hour, respectively. Unlike CO2 laser the deep melting mode is realized during evaporation of 1%Nd:Y2O3 and Al2O3 targets by fiber laser. The crater depth increases up to 300–1000 μm in this mode. As a result, the target surface became very irregular and productivity of nanopowder synthesis was less, than in the case of CO2 laser. To reduce the effect of deep melting the evaporation of a target has been investigated experimentally and theoretically. As a result of our investigations we have obtained 1%Nd:Y2O3 nanopowder with specific surface of 70 m2/g and productivity of 23 g/hour at air pressure 70 kPa. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)